KESANTUNAN EKSKLAMATIF DALAM WACANA DEMO RUU KUHP PADA KOLOM KOMENTAR MEDIA SOSIAL INSTAGRAM KABAR_KAMPUNG_KITO_ BULAN SEPTEMBER TAHUN 2019 - Dian Intan Suryani; Sainil Amral; Uli Wahyuni (Universitas Batanghari, 2020)
The purpose of this research is to describe the exclamatory politeness on aspects of form and function in the Wacana Demo RUU KUHP on Instagram Social Media Commentary Column kabar_kampung_kito_ on September 24th and 25th, 2019 (A Pragmatic Study). This research is qualitative descriptive. The results of the research showed that there are fifty expressions which consist of the form and function of exclamatory politeness. There are eighteen expressions of exclamative politeness. The most dominant type is the use of –nya which consisted of sixteen expressions. This particle was a complement to the subject in front of it. An expression of alangkah describes an event while another expression is a form of bukan main. There are thirty-seven expressions of exclamative functions. The most dominant type is the function of seruan which describes solicitations, calls, and warnings consisting of twenty expressions. While there are seventeen expressions of admiration that illustrate admirable circumstances.